Program English Tren dalam Mengenbangkan Kemampuan Speaking Santri Dalam Menghadapi Tantangan Global - Naeli Rosyidah; Slamet Pambudi; Prima Septyo Wibowo (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
Today, international communication plays a vital role for facing the global challenges and English as Lingua Franca is quite helpful to serve the purpose of communication with people from different countries. In pesantren world, English is very essential to teach and â€œEnglish-Trenâ€ can be a way of asssisting santri to develop the santrisâ€™ speaking skill. â€œEnglish-Trenâ€ is English for Pesantren, a branch of English for Specific Purposes (ESP), designed to meet the target of Pesantren in improving Santrisâ€™ English skills especially speaking. This study aims to explain how is English-Tren implemented in developing santrisâ€™ English Speaking Skill. This study is a case study with the setting in Pondok Pesantren Darussalam Dukuhwaluh Purwokerto promoting the santrisâ€™ improvement in speaking skill through the course of â€œEnglish-Trenâ€. The data collection techniques included interview to three English teachers and five santris supported by observation and documentation. The result shows that English-Tren is implemented through three ways namely Morning English biweekly, English taught as a subject in madrasah diniyah classes, and English taught and practiced in English program. Hence, English-Tren is influential in developing santrisâ€™ English speaking skill.